Ultrafast Size Expansion and Turn‐On Luminescence of Atomically Precise Silver Clusters by Hydrogen Sulfide - He, Wei‐Miao; Zhou, Zhe; Han, Zhen; Li, Si; Zhou, Zhan; Ma, Lu‐Fang; Zang, Shuang‐Quan (Angewandte Chemie International Edition, 2021)
The formation of high‐nuclearity silver(I) clusters remains elusive and their potential applications are still underdeveloped. Herein, we firstly prepared a chain‐like thiolated AgI complex {[Ag18(StBu)10(NO3)8(CH3CN)2(H2O)2] ⋅ [Ag18(StBu)10(NO3)8(CH3CN)6]}n (abbreviated as Ag18) in which two similar Ag18 clusters are assembled by NO3− anions. The solution containing Ag18 reacted with hydrogen sulfide with controlled concentration, promptly producing another identifiable and bright red‐emitting high‐nuclearity silver(I) cluster, Ag62(S)13(StBu)32(NO3)4 (abbreviated as Ag62). We tracked the transformation using time‐dependent electrospray ionization mass spectrometry (ESI‐MS), UV/Vis absorption and photoluminescence spectra. Based on this cluster transformation, we further developed an ultra‐sensitive turn‐on sensor detecting H2S gas with an ultrafast response time (30 s) at a low detection limit (0.13 ppm). This work opens a new way of understanding the growth of metal clusters and developing their luminescent sensing applications. Two similar Ag18 clusters are assembled via NO3− anions to form a chain‐like thiolated AgI complex (abbreviated as Ag18). The solution containing Ag18 reacted with H2S with controlled concentration, promptly producing another identifiable and bright red‐emitting high‐nuclearity silver(I) cluster Ag62. Based on this cluster transformation, an ultra‐sensitive turn‐on sensor was developed to the detection of H2S gas with an ultrafast response time (30 s) at a low concentration (0.13 ppm).